Functional analysis of glycosylation of Zika Virus envelope protein - Fontes-Garfias, Camila R (2017)
Zika virus (ZIKV) infection causes devastating congenital abnormities and Guillain-Barre´ syndrome. The ZIKV envelope (E) protein is responsible for viral entry and represents a major determinant for viral pathogenesis. Like other flaviviruses, the ZIKV E protein is glycosylated at amino acid N154. To study the function of E glycosylation, we generated a recombinant N154Q ZIKV that lacks the E glycosylation and analyzed the mutant virus in mammalian and mosquito hosts. In mouse models, the mutant was attenuated, as evidenced by lower viremia, decreased weight loss, and no mortality; however, knockout of E glycosylation did not significantly affect neurovirulence. Mice immunized with the mutant virus developed a robust neutralizing antibody response and were completely protected from wild-type ZIKV challenge. In mosquitoes, the mutant virus exhibited diminished oral infectivity for the Aedes aegypti vector. Collectively, the results demonstrate that E glycosylation is critical for ZIKV infection of mammalian and mosquito hosts.